PEMANFATAAN TEKNOLOGI INFORMASI DALAM PEMBERDAYAAN PENGERAJIN KAPAL KAYU DI KABUPATEN BATANG - Martono, Kurniawan Teguh (Jurnal Sistem Komputer, 2017)
Batang regency is one of the regency located in the north coast of Java in the province of Central Java. This district has various potentials that can be used as a regional superior potential. One of the potentials owned by Batang district is the wooden ship production area. This area is located in the north of the stem, namely Senturi area. Utilization of information technology or computer technology has not been widely used in ship production process. The production capability of ships made by this group is obtained from generation to generation or based on the experience of each member. This condition certainly causes problems in the process of resource management both from human resources and resources. Shipyard resource management information systems can be implemented in the woodcraft craftsman community. The results of both the functionality and the usability test show that the results are aligned where the design and test results have been appropriate. In the usability testing it is found that community groups can master the use of the system.